2009
DOI: 10.1007/s00359-009-0422-y
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for melatonin-linked immunoenhancement over the annual cycle of an avian species

Abstract: The winter immunoenhancement hypothesis associates long nights and increased exposure to melatonin with enhanced immune function in winter when resource availability is low and the chances of becoming ill are high. Thus, increased exposure to melatonin in the winter could be adaptive for species facing diYcult winter conditions. This idea has found some support in studies of resident mammals. In birds, the link between day length and melatonin over the annual cycle is weaker, and contributions of melatonin to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Melatonin cycles changed over the annual cycle, but the seasonal course did not fully support damping during particular life-cycle stages as had been shown for migratory songbirds (Gwinner and Brandstätter, 2001;Gwinner et al, 1993), nor did it simply reflect the amount of available daylight. Our findings add to heterogeneous evidence for links between light availability and melatonin in birds (Buehler et al, 2009;Gwinner and Brandstätter, 2001;Miché et al, 1991;Reierth et al, 1999;Silverin et al, 2009). Moonlight apparently exerted a mild, damping influence on melatonin (Tarlow et al, 2003), Fig.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Melatonin cycles changed over the annual cycle, but the seasonal course did not fully support damping during particular life-cycle stages as had been shown for migratory songbirds (Gwinner and Brandstätter, 2001;Gwinner et al, 1993), nor did it simply reflect the amount of available daylight. Our findings add to heterogeneous evidence for links between light availability and melatonin in birds (Buehler et al, 2009;Gwinner and Brandstätter, 2001;Miché et al, 1991;Reierth et al, 1999;Silverin et al, 2009). Moonlight apparently exerted a mild, damping influence on melatonin (Tarlow et al, 2003), Fig.…”
Section: Resultssupporting
confidence: 76%
“…1; for details, see Buehler et al, 2009;Piersma et al, 2000). 1; for details, see Buehler et al, 2009;Piersma et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Photoperiod is also known to promote extra feeding, fattening and migratory restlessness at appropriate dates for the population concerned [46], resulting in rhythmic behavior, metabolism, and physiological events [40]. However, this melatonin function is not universal in birds [47], change in amplitude of melatonin secretion could also be reduced during migration season despite constant photoperiod, resulting from physiological changed[45]. Future experimental studies are needed to validate our suggestion.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, we may suggest that variation in peripheral melatonin by natural light (Gwinner and Scheuerlein, 1998) conditions acts as a bolster to the immune function, on one hand, and suppressed the gonadal activity in winter, on the other hand, to help the individuals to have more energy to fight with seasonal stressors (Nelson and Drazen, 1999). Surprisingly, in the Red Knot (Calidris canutus), Buehler et al (2009) found no such correlation and suggested that immunocompromise should be correlated with the severity of the environment rather than the time of year. Therefore, variation in lung associated immune status noted throughout the year in P. asiatica of tropical zone might be responsible for adaptations that have evolved to decrease the odds of respiratory system in changing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%